Formative variables of trustworthiness on Instagram online sellers - Ascaryan Rafinda; Agus Suroso; Ascariena Rafinda; Putri Purwaningtyas (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2018)
This research aims to develop an indicator of trust in Online Seller Application Instagram. Instagram is a sharing picture application that used uniquely by Indonesian as a medium for a seller and buyer to meet. Deception was the biggest risk when people used online shopping. This study identifies an indicator of trustworthiness in Instagram Online seller application. Four indicators were proposed and proven could measure trust in online sellers. There are some followers, price rationality, image quality and seller response. Samples from this study were users of Instagram Online users. Total 20 informants for qualitative study and 488 respondents for the quantitative study participated in this research. This research used the mixed method. A qualitative method to identify and classify potential indicator for trustworthiness on Instagram seller, while quantitative method was used to measure the construct validity and reliability of trustworthiness on instagram online seller. The result show that from 12 indicators that represent trustworthiness in instagram online seller, it could classify into four variables by using Exploratory Factors Analysis (EFA). This research imply for Instagram seller, they should pay attention to factors that found by this research to gain trust from the customers.